Empowerment Of Farmer Group In Improving Chilli Farming Income In Kerinci District, Indonesia - Indra Karim; Hani Sri Handayawati; Wiwiek Ruminarti (Sekolah Pascasarjana Universitas Brawijaya, 2012)
Purpose of the agricultural development is to raise the quality of human resources and the livelihood of farmers and their families. The role of farmer groups are very important in supporting the agricultural intensification program, but their ability to adopt new technologies are still very limited. Base on these facts then problems of this research is role of the chilli farmers group empowerment in improving the farming revenues.The research was carried out in the Air Hangat Timur Subdistrict, Kerinci District, many farmers who insist the chili farming traditionally, they have not implemented the recommended agrotechnologies package. The number of samples as much as two groups of farmers, including 28 farmers from the Pinang-Jaya farmers group and 17 farmers from Usaha-Sepakat farmer groups. To find out the improvement level of farmers ability in improving farmer income, it is conducted the Coefficient Spearman test.The results showed that the ability of chilli agrotechnology implementation is included in the category of â€œintermediateâ€. There is a strong relationship between farmer age, educational level, experience farming and the number of family member with the farmer capability in implementing chilli agrotechnologies. Keywords: farmer group, chili farming, farming income